Relationship between land use and water quality in a subtropical river basin - De-Carli, Bruno Paes [UNESP]; De Souza, José Carlos [UNESP]; De Sousa, Jocy Ana Paixão [UNESP]; Shoegima, Thiago Franco; Barreiro, Maria Del Pilar Romero [UNESP]; Dutra, Ana Carolina [UNESP]; De Medeiros, Gerson Araújo [UNESP]; Ribeiro, Admilson Írio [UNESP]; Bressane, Adriano [UNESP] (My University, 2018)
This study investigated the influence of land use on water quality parameters in the subtropical basin of Jundiaí-Mirim river. Water samples were collected to measure nutrients concentration and direct measurements by multiparameter probe were performed, as well as landscape analysis, using satellite images and visits in the sampling sites, besides analysis of population density data. Data were standardized and the correlation between the variables was measured using Spearman approach. Land use in the surrounding area of the sampling points had strong and significant correlations (p < 0.05) with some of the water quality parameters evaluated. These correlations had different causes, explained by the land use in a 50 m radius, or 500 m radius, or even beyond these environments studied. Landscape analysis has proved to be an important tool for understanding the interaction between water quality and land use.
Keywords: Geoprocessing; Jundiaí-mirim river basin; Landscape analysis